The Victimological Context on Child Sexual Violence - Chasanah, Anissaa Nuril; Arifin, Ridwan (Universitas Islam Negeri Walisongo Semarang, 2022)
Sexual violence against children is a crime that needs serious attention. In this crime, children as victims often do not get adequate legal protection and fulfill their rights as victims. This study aims to analyze child sexual crimes in the context of victimology and victim protection. This study uses a normative legal study approach by analyzing the applicable laws and regulations as well as literature review related to the protection of children as victims of sexual crimes. This study proves and confirms that the protection of children in cases of sexual crimes has been legally guaranteed through the Law on the Protection of Witnesses and Victims, the Law on Child Protection, and the Law on Human Rights. However, the process of fulfilling the rights of children as victims in these crimes does not yet have adequate aspects of justice for children. The existing criminal law instruments are only oriented towards punishment and deterrence of perpetrators of sexual crimes. Kekerasan seksual terhadap anak menjadi salah satu tindak pidana yang perlu mendapatkan perhatian serius. Pada tindak pidana ini, anak sebagai korban seringkali tidak mendapatkan perlindungan hukum dan pemenuhan hak-haknya sebagai korban secara memadai. Studi ini bertujuan untuk menganalisis kejahatan seksual anak dalam konteks viktimologi dan perlindungan korban. Studi ini menggunakan pendekatan studi hukum normatif dengan menganalisis aturan perundang-undangan yang berlaku serta kajian kepustakaan berkaitan dengan perlindungan anak sebagai korban kejahatan seksual. Studi ini membuktikan dan menegaskan bahwa perlindungan anak dalam kasus kejahatan seksual telah dijamin secara yuridis melalui Undang-Undang Perlindungan Saksi dan Korban, Undang-Undang Perlindungan Anak, dan Undang-Undang Hak Asasi Manusia. Namun demikian proses pemenuhan hak-hak anak sebagai korban dalam tindak pidana tersebut belum memiliki aspek keadilan yang memadai bagi anak. Instrumen hukum pidana yang ada hanya berorientasi terhadap pemidanaan dan penjeraan terhadap pelaku kejahatan seksual.